CROSS-REACTIVITY OR DUAL INFECTION OF CHIKUNGUNYA AND DENGUE IN AN ENDEMIC AREA OF DENGUE - Dr. Shripad Taklikar; Dr. Pradnya Kale; Dr. Arghadip Samaddar; Dr. Sujata Baveja (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Dengue and Chikungunya are significant mosquito-borne viral infections endemic in India, transmitted primarily by Aedes aegypti and Aedes albopictus mosquitoes. Due to shared vectors and overlapping symptoms, co-infections and cross-reactivity between these viruses pose diagnostic challenges.Objectives: To determine the prevalence of cross-reactivity or dual infection of Dengue and Chikungunya viruses in an endemic area and compare findings with previous studies.Methods: A cross-sectional study was conducted from October to December 2017 at Lokmanya Tilak Municipal Medical College and General Hospital (LTMMC & GH), Sion, Mumbai. A total of 300 patients clinically suspected of Dengue infection were tested for Dengue NS1 antigen and IgM antibodies using ELISA. Confirmed Dengue-positive samples were further tested for Chikungunya IgM antibodies using ELISA. Data were analyzed and compared with findings from previous studies.Results: Out of 300 suspected cases, 121 (40.33%) were confirmed positive for Dengue infection. Among these, 51 (42.15%) samples were positive for Chikungunya IgM antibodies. The highest co-positivity was observed in patients with 4-7 days of fever duration (50%). These findings are higher compared to previous studies reporting co-infection rates ranging from 6% to 22%.Conclusion: A significant proportion of Dengue-confirmed patients also tested positive for Chikungunya IgM antibodies, indicating considerable cross-reactivity or dual infection in the studied region. This emphasizes the need for accurate differential diagnosis using advanced molecular techniques to ensure appropriate clinical management.